Tingkat Kepuasan Konsumen Pada Bungkoez Cafe Kota Manado - Damanik, Gracilia Jane; Benu, Noortje Marsellanie; Rengkung, Leonardus Ricky (Sam Ratulangi University, 2024)
This study aims to analyze the level of customer satisfaction at Bungkoez Cafe Manado City seen from the aspects of product, price, promotion, place and service. This research was conducted for 4 months, from October 2023 to February 2024, at Bungkoez Cafe Manado City. The data collection method was collected using primary data obtained through direct observation in the field, by conducting observations and interviews with cafe owners, employees and consumers, as well as giving questionnaires to consumers to fill out. Secondary data is obtained from internet sites, books, articles, research journals and various other documents related to the research. The sampling method for Bungkoez Cafe consumers used accidental sampling method, the number of samples obtained was 45 consumers based on a time limit of 5 days consisting of 3 working days and 2 holidays with respondents around 7-9 people per day. The analysis method used in this research is descriptive analysis, analyzing the answers obtained from the questionnaire, calculating the Likert Scale method, and analyzing the characteristics of each research variable using the index formula in each aspect of the marketing mix. The results showed that the results of the index number of customer satisfaction levels at Bungkoez Cafe Manado City in terms of product, price, location, promotion and service were at 80.86%, this shows that overall the manager of Bungkoez Cafe Manado City has reached the level of customer satisfaction even though there are still several indicators that need attention.